2005
DOI: 10.1176/foc.3.3.396
|View full text |Cite
|
Sign up to set email alerts
|

Guideline Watch: Practice Guideline for the Treatment of Patients With Borderline Personality Disorder

Abstract: Since the 2001 publication of APA's Practice Guideline for the Treatment of Patients With Borderline Personality Disorder (1), more studies have been published on borderline personality disorder (BPD) than on any other personality disorder (2, 3). New analyses of the validity of the DSM-IV-TR criteria-defined construct of BPD have been published, new data on the prevalence of BPD are available, risk factors for and biological characteristics of BPD are being elucidated, and new studies on the treatment of BPD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(82 citation statements)
references
References 78 publications
(63 reference statements)
1
76
0
5
Order By: Relevance
“…In accordance with the results of systematic reviews and treatment guidelines for the management of BPD, options to treat this disorder include both pharmacotherapy and psychotherapy (American Psychiatric Association, 2001;Oldham, 2005;NICE, 2009;NHMRC, 2012;Stoffers et al, 2012) and combination of them can be considered a valid approach in treating this clinical population (American Psychiatric Association, 2001;Oldham, 2005). Some authors suggested that psychotherapy may enhance pharmacotherapy effects, although it remains unclear how this treatments actually interact (Lieb et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with the results of systematic reviews and treatment guidelines for the management of BPD, options to treat this disorder include both pharmacotherapy and psychotherapy (American Psychiatric Association, 2001;Oldham, 2005;NICE, 2009;NHMRC, 2012;Stoffers et al, 2012) and combination of them can be considered a valid approach in treating this clinical population (American Psychiatric Association, 2001;Oldham, 2005). Some authors suggested that psychotherapy may enhance pharmacotherapy effects, although it remains unclear how this treatments actually interact (Lieb et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A similar set of self-assessment tools for the treatment of depression among adults was published earlier (39), guided by recommendations from the APA Practice Guideline for the Treatment of Patients with Major Depressive Disorder (40).…”
Section: Final Grade Of Recommendationmentioning
confidence: 99%
“…The Healthcare Effectiveness Data and Information Set (HEDIS) measures of the National Committee for Quality Assurance (NCQA) (40) are a commonly used group of quality indicators that measure health organization performance. anti-manic agent such as valproate or lithium."…”
mentioning
confidence: 99%
“…APA guidelines and fol lowing updates [1,66] recommended to choose antidepressant agents (SSRIs and MAOIs) and mood stabilizers as first and secondline inter ventions for affective dysregulation, SSRIs and mood stabilizers for impulsivebehavioral dys control, and antipsychotics as firstline therapy for cognitiveperceptual symptoms.…”
Section: Treatment Guidelines and Meta-analysesmentioning
confidence: 99%